ChemInform Abstract: 5‐Hydroxypyran‐4‐one Derivatives as Potential Therapeutic Iron—Chelating Agents. Issue 26 (June 2016) - Li, Junpei; Abbate, Vincenzo; Jurach, Jagoda; Zhang, Guoqing; Kong, Xiaole; Hider, Robert C.
Abstract: Mannich condensations of different amino compounds with formaldehyde and kojic acid gives tridentate chelators (IV) and (VI) and a hexadentate chelator (VII) which all possess a high affinity for Fe 3+ ‐ions.